"Red Vienna" and the rise of the populist right. (January 2022) - Essletzbichler, Juergen; Forcher, Johannes
While research on the spatial variation in populist right voting focuses on the role of "places left behind", this paper examines the spatial distribution of populist right voting in one of the fastest growing capital cities of Europe, Vienna. Combining detailed electoral data of the 2017 national elections at the statistical ward level and the location of municipal housing units, the paper examines why the populist right "Austrian Freedom Party" (FPOE) performs better in the former bulwarks of socialism, in the municipal housing areas of "Red Vienna". The paper links the socio-demographic development of Vienna and its municipal housing policy with election results and explores three possible reasons for elevated FPOE shares in municipal housing areas: rising housing costs pushed an increasing number of socially and economically vulnerable into the municipal housing sector and so increased the FPOE voter pool in those areas; European Union accession and changes in regulation allowed foreign citizens to apply to and obtain municipal housing flats triggering a backlash from Austrian municipal housing residents; and municipal housing is located in disadvantaged neighbourhoods further enhancing the FPOE voter pool. The paper demonstrates that higher FPOE vote shares in areas with high municipal housing shares are due primarily to higher shares of formally less educated residents, neighbourhood context and they are marginally elevated in those municipal housing areas experiencing a larger influx of foreign residents.